2023
DOI: 10.1101/2023.09.07.556720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling sources of clock-like mutations in germline and soma

Natanael Spisak,
Marc de Manuel,
William Milligan
et al.

Abstract: The rates of mutations vary across cell types. To identify causes of this variation, mutations are often decomposed into a combination of the single base substitution (SBS) “signatures” observed in germline, soma and tumors, with the idea that each signature corresponds to one or a small number of underlying mutagenic processes. Two such signatures turn out to be ubiquitous across cell types: SBS signature 1, which consists primarily of transitions at methylated CpG sites caused by spontaneous deamination, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…About 90% of human germline mutations have been attributed to a process known as SBS5 in the Catalog of Somatic Mutations in Cancer (COSMIC) database, while the remaining 10% are mostly attributed to a process known as SBS1 (38, 39). Both SBS1 and SBS5 have been classified as “clocklike” mutational signatures based on the correlation of their exposures with age in tumor data, though they are not clocklike with respect to the same time unit.…”
Section: Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About 90% of human germline mutations have been attributed to a process known as SBS5 in the Catalog of Somatic Mutations in Cancer (COSMIC) database, while the remaining 10% are mostly attributed to a process known as SBS1 (38, 39). Both SBS1 and SBS5 have been classified as “clocklike” mutational signatures based on the correlation of their exposures with age in tumor data, though they are not clocklike with respect to the same time unit.…”
Section: Model and Resultsmentioning
confidence: 99%
“…In contrast, SBS1 is dominated by CpG>TpG transitions caused by deamination of methylcytosine. While SBS1 was once thought to accumulate at a constant rate per year based on phylogenetic substitution data (41), de novo mutation data have since suggested that the load of SBS1 actually scales with the number of cell divisions, with little to no activity in post-mitotic cells but commensurately high activity in cells that are rapidly dividing (39, 40). The clocklike nature of these processes explains the mutagenic effect of generation time within species, since longer generations tend to span both more time and more cell divisions than shorter generations, leaving more time for SBS1 and SBS5 to accumulate.…”
Section: Model and Resultsmentioning
confidence: 99%
“…Among the 409 variants detected in 6 samples (2 each by 3 different fragmentation methods -no fragmentation, enzyme, and ultrasonication), nine mutation signatures, namely single base substitutions (SBS) SBS1, SBS3, SBS5, SBS7a, SBS10b, SBS30, SBS51, SBS58 and SBS87, were detected. Signatures SBS1 and SBS5 are recognized as being linked to the cell division/mitotic clock in most cancers 28,29 and were reported as the prevalent signatures across the various cancers 30,31 . Intriguingly, SBS30 was most prominently observed in the non-shared mutations, particularly evident in cases of enzyme fragmentation (Fig.…”
Section: Impact Of Fragmentation Methods On Mutation and Mutation Sig...mentioning
confidence: 99%
“…Tobacco smoke is known to affect the accumulation of de novo micro/minisatellites 6 , but its effects on de novo point mutations, the best-characterised form of genetic variation, have not yet been studied. Genetic factors may also influence germline mutation rate 7 . Rare variants in DNA repair genes are well-known modifiers of somatic mutation rates and spectra 810 , and have been shown to contribute to elevated rates of germline mutation 4,10 .…”
Section: Main Textmentioning
confidence: 99%